"No one can budge me away from this noble objective" - a community group responds to the COVID-19 pandemic in India. Issue 1 (2nd January 2022) - Alam, Iftekhar
ABSTRACT: The coronavirus pandemic brought misfortune to low-income households throughout India. This narrative describes the proactive responses of community group to the challenges posed by the COVID-19 pandemic and its consequent nation-wide lockdown that resulted into high influx of migrant laborers back home. The adversities of the lockdown led to a community group serving the less privileged in the community.